2014
DOI: 10.1038/nature12961
|View full text |Cite
|
Sign up to set email alerts
|

The genomic landscape of Neanderthal ancestry in present-day humans

Abstract: Analyses of Neandertal genomes have revealed that Neandertals have contributed genetic variants to modern humans1–2. The antiquity of Neandertal gene flow into modern humans means that regions that derive from Neandertals in any one human today are usually less than a hundred kilobases in size. However, Neandertal haplotypes are also distinctive enough that several studies have been able to detect Neandertal ancestry at specific loci1,3–8. Here, we have systematically inferred Neandertal haplotypes in the geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

99
1,287
13
25

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 949 publications
(1,463 citation statements)
references
References 38 publications
99
1,287
13
25
Order By: Relevance
“…Recent studies have revealed several mechanisms, including introgression, that can lead to adaptive divergence, especially in rapidly radiating groups (Pease et al 2016). There are numerous striking examples of adaptive introgression in plants, animals and humans that illustrate functional introgressed loci contributing to ecologically and reproductively significant traits (Whitney et al 2006; Song et al 2011; Sankararaman et al 2014; Lamichhaney et al 2015). Epichloë spp., grass endophytes in Hypocreales, contain many species that have evolve through a complex process of hybridisation (Moon et al 2004), indicating there is high possibility for the occurrence of introgression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed several mechanisms, including introgression, that can lead to adaptive divergence, especially in rapidly radiating groups (Pease et al 2016). There are numerous striking examples of adaptive introgression in plants, animals and humans that illustrate functional introgressed loci contributing to ecologically and reproductively significant traits (Whitney et al 2006; Song et al 2011; Sankararaman et al 2014; Lamichhaney et al 2015). Epichloë spp., grass endophytes in Hypocreales, contain many species that have evolve through a complex process of hybridisation (Moon et al 2004), indicating there is high possibility for the occurrence of introgression.…”
Section: Introductionmentioning
confidence: 99%
“…Afin d'estimer l'intensité du flux de gènes archaïques dans le génome des populations humaines, diverses méthodes ont été développées. Leur application a révélé que l'introgression n'est pas homogène le long du génome des populations européennes et asiatiques, suggérant que l'ADN archaïque introgressé a été soumis à différentes pressions de sélection [14]. Ainsi, certaines régions telles que l'ensemble du chromosome X, le bras q du chromosome 8 ou les séquences codantes prises dans leur ensemble, sont pauvres en allèles néandertaliens.…”
Section: Les Pathogènes Principale Contrainte Sélectiveunclassified
“…Ainsi, certaines régions telles que l'ensemble du chromosome X, le bras q du chromosome 8 ou les séquences codantes prises dans leur ensemble, sont pauvres en allèles néandertaliens. Si la pauvreté du chromosome X en allèles introgressés semble liée à une baisse de la fertilité des mâles issus des croisements entre Homo sapiens et hommes de Néandertal, il existe plus généralement une corrélation significative entre la forte densité en éléments fonctionnels présents dans le génome et la faible probabilité d'ascendance néandertalienne des allèles retrouvés dans ces régions [14]. Une partie de la diversité géné-tique acquise par introgression a donc eu des effets délétères sur les hommes modernes et a, par conséquent, été éliminée par la sélection purificatrice [14,15].…”
Section: Les Pathogènes Principale Contrainte Sélectiveunclassified
See 2 more Smart Citations